Investigation of Relationships between Self Efficacy and Scientific Epistemological Beliefs of Students in Physical Education and Sports - Eroğlu, Sultan Yavuz; Karayol, Metin (Asian Journal of Education and Training, 2020)
This study aims to investigate the relationship between general self-efficacy and scientific epistemological beliefs of the students in the school of physical education and sports. The study group consists of 400 students (174 female, 226 male) in total. Personal information form created by researchers and “Scientific Epistemological Beliefs Scale" transcribed to Turkish by Acat, Gülçin, and Karadağ (2010) and “Self Efficacy Scale" transcribed to Turkish by Yeşilay (1996) has been used as a data collector in the study. In the analysis of data, the T-test has been used in the comparison of quantitative continuous data between two independent groups and the One Way Anova test has been used in the comparison of quantitative continuous data between more than two independent groups. Scheffe test has been used as the completive post hoc analysis to determine the differences after the Anova test. Pearson correlation test has been implemented between the continuous variables of the study. As a result of the study, it has been seen that there is a significant difference on behalf of the ones who are 20 years old and over informing information as one of the scientific epistemological sub-dimensions on behalf of the students of Bingöl University (p<0.05). It has been also seen that there is a significant difference on behalf of Ankara University students and females in the gender variable in general self-efficacy points (p<0,05). It has not been seen that there is a significant difference in other variables (p>0.05).